A thirsty sparrow how can he drink water from the glass? - Almario, Virgilio S.; Torres, Jimmy (Quezon City Adarna House, 2003)
This old fable shows how problems can be solved through careful thinking. Besides being a lesson in science, the story also teaches basic counting skills.
Rekomendado sa mga batang edad 7 pataas.